Particle arc therapy: status and potential - Mein, Stewart; Wuyckens, Sophie; Li, Xiaoqiang; Both, Stefan; Carabe, Alejandro; Vera, Macarena Chocan; Engwall, Erik; Francesco, Fracchiolla; Graeff, Christian; Gu, Wenbo; Hong, Liu; Inaniwa, Taku; et al. (Radiotherapy and oncology, 2024)
There is a rising interest in developing and utilizing arc delivery techniques with charged particle beams, e.g., proton, carbon or other ions, for clinical implementation. In this work, perspectives from the European Society for Radiotherapy and Oncology (ESTRO) 2022 physics workshop on particle arc therapy are reported. This outlook provides an outline and prospective vision for the path forward to clinically deliverable proton, carbon, and other ion arc treatments. Through the collaboration among industry, academic, and clinical research and development, the scientific landscape and outlook for particle arc therapy are presented here to help our community understand the physics, radiobiology, and clinical principles. The work is presented in three main sections: (i) treatment planning, (ii) treatment delivery, and (iii) clinical outlook.